ESTIMATION OF CLINICAL AND PHARMACOKINETIC EQUIVALENCE OF ORIGINAL AND GENERIC CARVEDILOLS IN PATIENTS WITH HYPERTENSION OF 1-2 GRADES - E. I. Bambysheva; S. N. Tolpygina; D. F. Guranda; I. E. Koltunov; V. G. Belolipetskaja; S. J. Martsevich (Столичная издательская компания, 2016)
Aim. To study clinical equivalence of original (DilatrendR, ≪Hoffmann-La Roche≫, Switzerland) and of generic (VedicardolR, ≪Synthesis≫, Russia) carvedilols with estimation of their serum level. And to study pharmacoeconomic advantages of their usage in patients with arterial hypertension (HT) of 1-2 stages.Material and methods. Study was double blind, randomized, crossed. 30 patients (8 men and 22 women, 57 y.o. average) with HT of 1 stage (3,3 %) and 2 stage (96,7 %) were included in the study. Original or generic carvedilols (12,5 mg twice a day) were prescribed to the patients. Hydrochlorothiazide was added followed carvedilol dose enlargement if initial antihypertensive effect had been insufficient. The second similar course of therapy with other carvedilol took place in 2 weeks after cancellation of the first carvedilol. Carvedilol serum level, blood pressure (BP), heart rate (HR) and side effects were registered on each visit.Results. 75 % of Vedikardol-group patients and 75 % of Dilatrend-group patients had reached target BP level (<140/90 mm Hg). Monotherapy was effective more than in a half of patients in both groups. Dilatrend had more expressed influence on HR in comparison with Vedikardol. Both drugs did not differ significantly in frequency and intensity of side effects.Conclusion. Generic carvedilol (VedicardolR) has clinical efficiency and pharmacokinetics similar to these of original carvedilol (DilatrendR). Generic carvedilol has lower cost of treatment than this in original carvedilol.